Studies in Convergence? Post‐Crisis Effects on Corporate Rescue and the Influence of Social Policy: The EU and the USA1. Issue 1 (23rd December 2015) - Gant, Jennifer L. L.
Abstract: The financial crisis and the sovereign debt crisis that it precipitated in a number of peripheral EU Member States heralded massive changes in insolvency, corporate rescue and employment protection policies. The US and the EU both suffered greatly in the wake of the crisis, but their recoveries have occurred along very different tracks. The US has managed to regain much of its position in terms of relative growth and the UK has outpaced the recoveries of those European countries that are members of the European Monetary Union. The purpose of this treatise is to explore the context of the 2007–2008 financial crisis in the US and in the EU and its impact on legal reform in corporate rescue and restructuring as well as those aspects of social policy implicated within insolvency systems (notably collective redundancy and transfers of undertakings). It will also consider whether or not the corporate rescue and employee protection systems can be seen to be converging, and whether, in view of the different socio‐economic, political and cultural aspects of the US and the EU, such convergence might be beneficial. Copyright © 2015 INSOL International and John Wiley & Sons, Ltd.